Inclusive EFL Teaching for Young Students with Special Needs: A Case in China - Jinjin Lu; Han Jiang; Yi Huang (MDPI AG, 2022)
In China, English as a foreign language is important and compulsory from primary education to higher education, essentially because English has become a global language. The Ministry of Education emphasizes that school principals should attempt to train teachers in special education and in assisting students with special education needs (SEN) in regular classes via supportive services. However, EFL teachers usually have insufficient training and do not know how to adjust their teaching methods for students with SEN in regular classes. This study investigated 328 teachers' teaching practices and their attitudes toward including students with SEN in K-12 English classes in the three largest provinces in east, south, and central China. The findings indicated that English teachers have not used specific teaching resources to teach students with SEN. Teachers noted that they were not provided with specialized training and there were not enough teaching assistants to help the students with SEN. There were significant statistical differences found between primary school teachers and middle school teachers with and without special education training regarding inclusion practices and their attitudes toward inclusion (regarding students with SEN). Most English teachers believe that students with SEN should be taught in special classes with specialized materials rather than in regular EFL classes.